Negosiasi Etika dan Estetika Konten TikTok Muslim dalam Perspektif Hukum Islam - Sarsil MR; Kurniati; Misbahuddin (Lembaga Yasin AlSys, 2026)
The development of TikTok has made algorithmic visibility, short-video aesthetics, and participatory culture important elements of contemporary Muslim expression. However, studies directly connecting the platform’s logic with Islamic legal ethics remain fragmented. This study aimed to analyze the negotiation of ethics and aesthetics in Muslim TikTok content and to formulate an evaluation framework based on maqāṣid al-syarī‘ah. This normative legal study employed a qualitative approach with a literature review design. The units of analysis comprised retrievable scholarly works on TikTok, digital religion, Islamic communication, content analysis, and Islamic legal theory, which were purposively selected based on their relevance to platform practices and normative evaluation. The data were organized into a literature matrix and subsequently analyzed through qualitative content analysis, legal interpretation, and comparative synthesis. The findings identified four main patterns: algorithmic aesthetics shapes visibility and imitative practices; ethical concerns arise in relation to informational accuracy, dignity, bodily representation, and monetization; digital religious authority becomes more accessible yet increasingly performative; and maqāṣid al-syarī‘ah provides contextual criteria for distinguishing between maṣlaḥah and mafsadah. This study concludes that aesthetic innovation is not inherently contrary to Islamic ethics but requires proportional boundaries based on the protection of religion, life and dignity, intellect, progeny, and property. The formulated evaluation matrix offers conceptual and practical contributions by bridging Islamic legal reasoning and platform-based digital culture in the evaluation of Muslim TikTok content.